Health organization in Colombia (1922)
This post first a presentation of history and geography of Colombia. Furthermore an overview of the problems concerned with health in Colombia. / Abstract. Esta publicación primero hace una presentación de la historia y geografía de Colombia. Por otra parte hace una reseña de la problemática que concierne a la salud en Colombia.